Development and preliminary validation of a new instrument to assess eating behaviors: The virtual self-service restaurant (VSSR) - Scoffier, S.; Gernigon, C.; Billi, E.; d`Arripe-Longueville, F. (Science & Sports, 2013)
Objectives: The aim of this study was to develop a computerized instrument to assess eating attitudes and behaviors, the "virtual self-service restaurant" (VSSR), and to test for preliminary evidence of its validity. Improved measures of self-regulation in this area should facilitate the management of individuals with eating disorders, particularly athletes, and the implementation of tailored prevention and intervention programs. Results: This interface assesses the individual's basal metabolism, energy expenditure related to physical activity, global energy expenditure, global energy intake (i.e., difference between energy expenditure and intake), and distribution of food intake over the day. The validity of the VSSR was tested in four populations, and the results indicated satisfactory internal and external validity. Conclusion: This instrument, which shows preliminary evidence of validity and reliability, can be used to promote educational nutrition programs for sedentary and athletic populations.